2013
DOI: 10.1016/j.bandc.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric lateralization of verbal and spatial working memory during adolescence

Abstract: Adult functional magnetic resonance imaging (fMRI) literature suggests that a left-right hemispheric dissociation may exist between verbal and spatial working memory (WM), respectively. However, investigation of this type has been obscured by incomparable verbal and spatial WM tasks and/or visual inspection at arbitrary thresholds as means to assess lateralization. Furthermore, it is unclear whether this hemispheric lateralization is present during adolescence, a time in which WM skills are improving, and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 69 publications
10
66
1
Order By: Relevance
“…This finding suggests that the magnitude of WM-related frontal activations may be an indicator of neural efficiency in processing verbal WM. Some neuroimaging studies have found that verbal WM was left-lateralized in the brain [26,75], whereas others have reported that it was processed bilaterally [30,76]. The present findings support the view that verbal WM is processed by the prefrontal cortices on both sides.…”
Section: Discussionsupporting
confidence: 86%
“…This finding suggests that the magnitude of WM-related frontal activations may be an indicator of neural efficiency in processing verbal WM. Some neuroimaging studies have found that verbal WM was left-lateralized in the brain [26,75], whereas others have reported that it was processed bilaterally [30,76]. The present findings support the view that verbal WM is processed by the prefrontal cortices on both sides.…”
Section: Discussionsupporting
confidence: 86%
“…Differences in corpus callosum anatomy such as reduced volume or reduced microstructural integrity are related to lower lateralization of function in typical participants and patient groups (Hinkley et al., 2016; Just, Cherkassky, Keller, Kana, & Minshew, 2007; Persson et al., 2006). In turn, lower lateralization is associated with lower performance on cognitive tasks, including executive function tasks (Hinkley et al., 2012; Just et al., 2007; Nagel, Herting, Maxwell, Bruno, & Fair, 2013). Similarly, posterior temporal white matter may provide connections for integration between specialized regions of temporal lobe for verbal and visuospatial working memory with the posterior parietal executive attention network.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of an association between WM and handedness may reflect the fact that verbal WM tasks are predominantly left hemisphere lateralized (e.g., Nagel, Herting, Maxwell, Bruno, & Fair, 2013;Wagner, Sziklas, Garver, & Jones-Gotman, 2009), and although some studies have also shown a bilateral involvement, these are strongly attributed to the use of visual strategies to remember the verbal WM material better (e.g., Gerton et al, 2004;Haut et al, 2000). Given that the handedness differences are presumed to reflect differential access to right hemisphere processes, it may be that the handedness groups do not differ in access to left hemisphere processing.…”
Section: Discussionmentioning
confidence: 99%